Session Topic: Financial Models of Regulated Firms: Discussion - Brennan, Michael J.; Carleton, Willard T.; Myers, Stewart C. (Journal of Finance, 1975)
Michael J. Brennan, Willard T. Carleton, Stewart C. Myers, Session Topic: Financial Models of Regulated Firms: Discussion, The Journal of Finance, Vol. 30, No. 2, Papers and Proceedings of the Thirty-Third Annual Meeting of the American Finance Association, San Francisco, California, December 28-30, 1974 (May, 1975), pp. 446-450